2019
DOI: 10.1038/s41598-019-44984-9
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mechanisms govern recalibration to audio-visual discrepancies in remote and recent history

Abstract: To maintain perceptual coherence, the brain corrects for discrepancies between the senses. If, for example, lights are consistently offset from sounds, representations of auditory space are remapped to reduce this error (spatial recalibration). While recalibration effects have been observed following both brief and prolonged periods of adaptation, the relative contribution of discrepancies occurring over these timescales is unknown. Here we show that distinct multisensory recalibration mechanisms operate in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 45 publications
3
33
1
Order By: Relevance
“…In terms of the temporal profile, the large immediate VAE and smaller persistent VAE observed here are generally consistent with the observations of multiple distinct cross-modal recalibration mechanisms reported in the horizontal VAE studies (Bosen, Fleming, Allen, O'Neill, & Paige, 2018;Watson, Akeroyd, Roach, & Webb, 2019). However, a signle adaptation mechanism cannot be ruled out for the current results given that the current study was not specifically designed to examine this question.…”
Section: Discussionsupporting
confidence: 89%
“…In terms of the temporal profile, the large immediate VAE and smaller persistent VAE observed here are generally consistent with the observations of multiple distinct cross-modal recalibration mechanisms reported in the horizontal VAE studies (Bosen, Fleming, Allen, O'Neill, & Paige, 2018;Watson, Akeroyd, Roach, & Webb, 2019). However, a signle adaptation mechanism cannot be ruled out for the current results given that the current study was not specifically designed to examine this question.…”
Section: Discussionsupporting
confidence: 89%
“…We found that prestimulus alpha activity predicts the degree of biasedness to perception after prolonged temporal recalibration, but does not mediate trial-by-trial recalibration, i.e., the influence of a previous response on behavior (Van der Burg et al, 2013). This suggests that distinct mechanisms underlie prolonged and single-trial recalibration, a conclusion supported by psychophysical experiments in the temporal (Van der Burg et al, 2015) and the spatial domains Röder, 2015, 2019;Watson et al, 2019). A role of alpha activity in reflecting an individual's overall perceptual tendency without interacting with trial-by-trial dependencies is also supported by a recent study on multisensory integration (Rohe et al, 2019).…”
Section: The Apparent Asymmetry Of Temporal Recalibrationmentioning
confidence: 64%
“…We found that pre-stimulus alpha power predicts biased perception after temporal recalibration, but does not mediate the effect of previous responses on behavior, suggesting that dissociated mechanisms underlie prolonged and single-trial recalibration. There is evidence from psychophysical experiments supporting this hypothesis in the temporal (Van der Burg, Alais, & Cass, 2015) and the spatial domain (Bruns & Röder, 2015;Bruns & Röder, 2017;Watson, Akeroyd, Roach, & S.Webb, 2019). A recent neuroimaging study showed that pre-stimulus alpha power predicted the tendency to bind audiovisual events, but played no role in mediating the influence of the recent history (Rohe, Ehlis, & Noppeney, 2019).…”
Section: Distinct Mechanisms Mediating Prolonged and Single-trial Recmentioning
confidence: 99%